2008
DOI: 10.1111/j.1532-5415.2008.02000.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Activity Counseling on Disability in Older People: A 2‐Year Randomized Controlled Trial

Abstract: The physical activity counseling intervention had no effect on older sedentary community-dwelling persons with a wide range of IADL disability, although it prevented incident IADL disability. The results warrant further investigation to explore the benefits of a primary care-based physical activity counseling program on decreasing and postponing IADL disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…It was hypothesized that physical activity counseling would increase physical activity, which in turn, would decrease mobility difficulties, postpone disability, and consequently decrease the need for home care. The current results complement the earlier findings on reduced mobility limitation 5 and the subgroup finding on reduced incident IADL disability 6 and indicate that the trial benefits may extend the entire length of the hypothesized pathway.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It was hypothesized that physical activity counseling would increase physical activity, which in turn, would decrease mobility difficulties, postpone disability, and consequently decrease the need for home care. The current results complement the earlier findings on reduced mobility limitation 5 and the subgroup finding on reduced incident IADL disability 6 and indicate that the trial benefits may extend the entire length of the hypothesized pathway.…”
Section: Discussionsupporting
confidence: 84%
“…A recent randomized controlled trial (RCT) showed that physical activity counseling decreased functional limitations in older people 5 . In addition, subgroup analyses showed a reduction in the incidence of instrumental activity of daily living (IADL) disability for those without IADL disability at baseline 6 . This letter presents results on the effect of physical activity counseling on formal home care use in older community‐dwelling sedentary persons.…”
mentioning
confidence: 96%
“…Many studies have investigated the relationship between physical activity and the prevention of chronic diseases (e.g., high blood pressure, depression, obesity, diabetes, osteoporosis, etc. ; Centers for Disease Control and Prevention [CDC], 2009;Oberg, 2007;Von Bonsdorff et al, 2008;Vuori, 2004). According to the CDC (1997, pg.…”
Section: Discussionmentioning
confidence: 99%
“…PA studies in older people often do not recruit enough participants to meet sample size requirements [19][20][21][22][23][24][25][26]. Only one FaME class per PSI was selected which limited the number of classes and participants reached.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%